A Complexity Analysis of User Interaction with Hotel Robots. (30th May 2020) - Zhong, Lina; Yang, Liyu; Rong, Jia; Li, Xiaonan
Abstract : Service robots have been introduced to hotel industry in the past decade and received various feedback on their performance. To provide better service, one needs to understand how the hotel customers look at the service robots. Understanding their interests, motivation, and behaviors in human-robot interaction is the key to develop high-quality services and improve robot's performance. This is the first work to study human-robot interaction in hotels in China. Frequent pattern mining and social network analysis techniques are used in this work to find out useful suggestions to both hotel management and robot manufactory. Turning on and off lights, TV, curtain, and window screens are popular services that most of the hotel customers preferred during their stays. Service robots are also found to entertain customers to carry out repeated commands for fun or to kill time. Customers also showed various motivations to stay in hotel rooms by calling different commands.